Examining the Links Between General Strain and Control Theories: an Investigation of Delinquency in South Korea - Choi, Jaeyong (Asian journal of criminology, 2019)
In modifying general strain theory (GST), Agnew has accepted the control-related variables as conditioning variables to moderate or mediate the casual process through strain into delinquency. In this regard, this study aims to empirically and theoretically address the void of connecting traditional and redefined self-control variables to GST. To explore this issue, the current study employed data derived from the Korea Children and Youth Panel Study (KCYPS). Specifically, three waves (2012, 2013, and 2014) were used to test hypotheses from GST and control theories. Both trait-based low self-control and revised self-control partially mediated the relationship between strain and delinquency. However, only redefined self-control significantly interacted with strain in producing delinquency. The current research reveals the possible integration of redefined control theory and GST.